Blockchain-Enabled Anti-Corruption Frameworks for Public Procurement: A Latin American Case Study - Silva Atencio, Gabriel (EAI Endorsed Transactions on Scalable Information Systems, 2025)
This research examines the potential application of blockchain technology in combating corruption in public procurement in Latin America, with a focus on Costa Rica's SICOP system. The research identifies systemic weaknesses in current processes and proposes a phased framework for the adoption of blockchain. It does this by using an exploratory qualitative approach that combines ethnographic case studies of procurement officials with a comparison of how things are done in other countries. Key results show that blockchain can fill in important gaps in bid verification, audit efficiency, and process transparency. They also show that there are cultural and organizational impediments to deployment that people don't realize. The study adds to the state of the art by (1) creating a context-specific implementation model that has been tested against problems in the region; (2) measuring how well blockchain works to fight corruption through real-world benchmarks; and (3) making policy suggestions for mixed technical-institutional reforms. The results show that blockchain's worth comes not just from its cryptographic capabilities but also from its capacity to make transparency a standard way of governing. However, for it to be effective, there has to be equal investment in modernizing the law, teaching people about ethics, and getting stakeholders involved. The study goes beyond just talking about theories by giving emerging economies useful information that takes into account both technology and human components in anti-corruption initiatives.
Keywords: Blockchain; corruption; governance; procurement; professional ethics; transparency